Development of Lao Writing Skills for Third-Year Kindergarten Students through Whole Language Approach - MAHALATH, Thipkesone; KEOBOUALAPHET, Soulideth; SIDAVONG, Khanthaly; KHAMPADITH , Shaidan; VONGPHACHANH, Vongphiboun (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
This research aims to 1) compare the students' Lao writing skills before and after the Whole Language Approach teaching experience, and 2) study the effectiveness of the Whole Language Approach teaching experience in developing Lao writing skills for kindergarten 3 students at the Khuannakhone Kindergarten-Primary School, Xayaburi District, Xayaburi Province, academic year 2024-2025. The target group for the experiment was selected by convenience without using criteria, namely male and female students aged 5-6 years old who were studying in kindergarten 3, grade 3/1, in the academic year 2024-2025 of the Khuannakhone Kindergarten-Primary School, Xayaburi District, Xayaburi Province, a total of 15 students. The research tools are divided into 2 categories: 1) Experimental tools include a natural language teaching experience plan that focuses on activities that create natural language learning experiences for students, and 2) data collection tools include a Lao writing skills test. The statistics used in the research are the mean, standard deviation, pair sample t-test, and effectiveness index using the SPSS computer program. The results of the research found that 1) the Lao writing skills for kindergarten 3rd grade students at the Khuannakhone Kindergarten-Primary School, Xayaburi District, Xayaburi Province after the natural language teaching experience is higher than the natural language teaching experience with P-value = 0.000, and 2) the effectiveness of the whole Language approach to develop Lao language writing skills for the kindergarten 3rd grade students is seen to have a good development up to 81.54%.